Multisensitive community-acquired methicillin-resistant Staphylococcus aureus infections in Malaysia - Sam, I.C.; Kahar-Bador, M.; Chan, Y.F.; Loong, S.K.; Ghazali, F.M.N. (2008)
The 1st 9 clinical isolates of multisensitive community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) from Malaysia carry SCCmec type IN and predominantly cause skin and soft-tissue infections. Seven were classified as nosocomially acquired. There was considerable clonal diversity, with both pandemic and novel multilocus sequence types detected. CA-MRSA rates appear to be increasing in our hospital, warranting close surveillance. (C) 2008 Elsevier Inc. All rights reserved.